The Vital Role of Pancasila Values in Building National Character Through Civics Education - Ana Andriani; Enok Maryani; Idrus Affandi (STAI Hubbulwathan Duri, 2023)
This paper inquires to look at the vital role of Pancasila values in building the nation's character of students through civic education. This research was conducted to see how far the role of Pancasila values as part of the Citizenship Education subject, apart from being a national ideology, is also a nation's view of life that can shape the nation’s character in students at school. This research used a qualitative and quantitative approach with a population of 21 high schools in Purwakarta with a sample of 5 schools as a sample. From this research, it was found that the Pancasila values contained in the first to the fifth precepts in the Civics Education subject are expected to be a guide for students in everyday life, both inside the classroom and outside the classroom, in the family, in the community, even in the life of the nation and state. As agents of social change, students must still be able to see the meaning of Pancasila's position as the basic foundation, which is the core of Civics learning, so that Pancasila's values can still be a guide in people's lives Pancasila and able to shape the character of the nation.